Manufacturers' dilemma falling into exclusive-offer competition: A laboratory experiment - Hiroshi Kitamura; Noriaki Matsushima; Misato Sato; Wataru Tamura (Osaka University, Institute of Social and Economic Research (ISER), 2025)
We experimentally investigate exclusive-offer competition between two existing upstream firms. In theory, when upstream firms make exclusive offers to a downstream monopolist, both exclusion and non-exclusion can be equilibrium outcomes. By varying key parameters, we explore how bargaining power and product differentiation affect the likelihood of exclusion outcomes. We experimentally find that exclusion is more likely to be observed when the upstream firms have stronger bargaining power or when they produce more differentiated products; paradoxically, the higher upstream firms' profits from cooperatively offering unattractive exclusive contracts, the more likely they are to fall into intense exclusive-offer competition.
Keywords: L12; L41; L42; 330; Exclusive dealing; Exclusive-offer competition; Bargaining Power; Product differentiation; Laboratory experiment